Biodiesel production from sludge palm oil by ultrasonic energy - Hayyan, Adeeb; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Mohd. Hakimi, Noor Irma Nazashida; Mohd. Siran, Yosri; Tahiruddin, Shawaluddin; Al-Saadi, Mohammed A. (2009)
The main challenges for biodiesel production are the cost of raw material (fats and oils) and the cost of processing. In this study free fatty acid (FFAs) of sludge palm oil has been converted to fatty acid methyl ester via acid-catalyzed reaction using ultrasonic energy. Batch esterification process of SPO was carried out to study the influence of sulfuric acid dosage (0.5, 1, 2% wt/wt), molar ratio of methanol to SPO (6:1, 10:1, 14:1), and temperature (50oC, 60oC, 70oC). The reduction of free fatty acids (FFAs) was measured at different sonication time from 30-300 min and the optimum time was determined. It is reasonable to conclude that the conversion of FFAs to fatty acid methyl ester by applying ultrasonic energy is related to long sonication time. The results showed that the FFA content of SPO reduced from 24.5% to less than 3 % using molar ratio 10:1, reaction temperature 50o C and 2% wt /wt sulfuric acid to SPO in 300 minutes sonication time.